Empirical risk analysis of pension insurance: the case of Germany - Christian Schmieder; Timo Reinschmidt; Ferdinand Mager; Wolfgang Gerke (Deutsche Bundesbank, 2006)
With this paper we seek to contribute to the literature on pension insurance systems. The financial literature tends to focus exclusively on the US pension insurance system. This is the first major empirical study to address the German occupational pension insurance (PSVaG) plan in Germany. The study is based on a Merton-type one-factor model, in which we determine the credit portfolio risk profile of the occupational pension insurance plan and compare two alternative pricing plans. We find that there is a low, yet non-negligible risk of very high losses that may threaten the existence of the occupational pension insurance plan (PSVaG). While relating risk premiums to firms' default probabilities would cause them to diverge widely, a marginal risk contribution method would produce less pronounced differences compared to the current, uniform pricing plan.
Keywords: G18; G28; C15; G22; G23; 330; Pension insurance; Risk-adjusted premiums; Credit portfolio risk; Betriebliche Altersversorgung; Kreditrisiko; Risikoprämie; Pensionsfonds; Schätzung; Deutschland